(untitled) (Czech Journal of International Relations, 1966)
Sometime in the late fifties, when the world began to talk more about peace and think less about war, the first scientists, groups, and institutes "for peace research" appeared in the USA and then in Europe. At American universities, some professors dealt with it, in Europe one of the leading institutes was the Peace Research Institute in Oslo (PRIO), opened in the summer of 1959. Research was created, in which experts from various scientific disciplines took part, not only social sciences (history , sociology, economics or so-called political science), but also exact ones (physicists, doctors, etc.). Although the subject of the research was questions from the field of international relations, into which any conflict situations between states or systems are immediately projected, but precisely because it is about questions of war and peace, existence andnon-existence of humanity, other scientists also applied.